BMP Signaling: Lighting up the Way for Embryonic Dorsoventral Patterning - Yan, Yifang; Wang, Qiang (Frontiers in Cell and Developmental Biology, 2021)
One of the most significant events during early embryonic development is the establishment of a basic embryonic body plan, which is defined by anteroposterior, dorsoventral (DV), and left-right axes. It is well-known that the morphogen gradient created by BMP signaling activity is crucial for DV axis patterning across a diverse set of vertebrates. The regulation of BMP signaling during DV patterning has been strongly conserved across evolution. This is a remarkable regulatory and evolutionary feat, as the BMP gradient has been maintained despite the tremendous variation in embryonic size and shape across species. Interestingly, the embryonic DV axis exhibits robust stability, even in face of variations in BMP signaling. Multiple lines of genetic, molecular, and embryological evidence have suggested that numerous BMP signaling components and their attendant regulators act in concert to shape the developing DV axis. In this review, we summarize the current knowledge of the function and regulation of BMP signaling in DV patterning. Throughout, we focus specifically on popular model animals, such as Xenopus and zebrafish, highlighting the similarities and differences of the regulatory networks between species. We also review recent advances regarding the molecular nature of DV patterning, including the initiation of the DV axis, the formation of the BMP gradient, and the regulatory molecular mechanisms behind BMP signaling during the establishment of the DV axis. Collectively, this review will help clarify our current understanding of the molecular nature of DV axis formation.